Influence of pig slurry characteristics on ammonia stripping efficiencies and quality of the recovered ammonium‐sulfate solution. Issue 9 (11th February 2013) - Laureni, Michele; Palatsi, Jordi; Llovera, Montserrat; Bonmatí, August
Abstract: BACKGOUND: Proper treatment technologies are required to address the environmental issues associated with increasing volumes of slurries. Ammonia stripping reduces the nitrogen content of the slurries and allows for its recovery in a valuable form. Herein the influence of pig slurry characteristics on ammonia stripping efficiency and the quality of the recovered ammonia solution were assessed . RESULTS: Substrates characterized by low organic matter content, below 10 g COD L ‐1, resulted in ammonia stripping efficiencies greater than 80%. Changing slurry pH to 9.5 significantly improved the process, even though high COD contents kept the efficiencies below 70%. Ammonium sulfate solutions could be concentrated up to nitrogen contents greater than 40 g N L ‐1, while maintaining low organic contamination. Introducing a basic trap (pH > 12) before the acid one, allowed for the retention of more than 60% of the stripped organics with less than 3% of the stripped ammonia . CONCLUSIONS: Ammonia stripping coupled with absorption proved to be a suitable technical solution for the recovery and valorization of the nitrogen contained in pig slurries. Clear enhancements in process efficiency were observed in the case of slurries with low organic matter content. The introduction of a basic trap, together with a slight increase in the operational pH level, further increased organics abatement. © 2012 Society of Chemical Industry